Level of General Stress in Doctors Community in Pre and Post Covid-19 Scenario in Different Hospitals of Pakistan - Nayyar, Shaista; Niaz, Asif; Abbas, Naseer Ahmed; Lashari, Naveed; Ahmad, Jawad; Khan, Shahid (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To find out the level of stress among the doctor community before and during the COVID-19 pandemic in different public sector hospitals.Study Design: Cross-sectional study.Place and Duration of Study: Divisional Headquarters DHQ Teaching Hospital, Sahiwal Pakistan and two Public Sector Hospitals at Okara and Islamabad Pakistan, from Aug 2019 to Aug 2020.Methodology: A total of 320 doctors in two Groups were included in the study. Group-1 included 197 doctors in pre-COVID-19 time i-e from Aug 2019 to Jan 2020, while Group-2 included 123 doctors working in the COVID-19 scenario. The stress was assessed according to responses on a structured questionnaire and patient health questionnaire (PHQ-9) scores.Results: Three hundred and twenty doctors participated in the study, out of which 78(39.8%) doctors in the First Group and 49(40.4%) in Second Group developed depression during their duties. More female doctors participated in the study, most of whom were young doctors who were actively involved in COVID-19 patients.Conclusion: There is no significant rise in stress among the doctors working in the COVID-19 situation in public sector hospitals of Pakistan.